Sentinel lymph node biopsy for 102 patients with primary cutaneous melanoma at a single Japanese institute. Issue 10 (13th June 2015) - Otsuka, Masaki; Yamasaki, Osamu; Kaji, Tatsuya; Iwatsuki, Keiji; Asagoe, Kenji
Abstract Sentinel lymph node biopsy (SLNB) is a widely accepted standard procedure for patients with clinically localized melanoma. Melanoma prevalence and Clark's subtype differ between Asians and Caucasians. Here, we evaluated our experience on SLNB for cutaneous melanoma in a Japanese population. SLNB was performed for patients with melanoma between July 2000 and June 2014. We retrospectively analyzed 102 patients regarding association of clinicopathological features with sentinel lymph node (SLN) status, melanoma‐specific survival (MSS) and disease‐free survival (DFS). A positive SLN was significantly associated with primary Breslow thickness. Compared with 43 patients with negative SLN, 59 patients with positive SLN had significantly shorter MSS (5‐year survival rate, 94.3% vs 63.2%; P = 0.0002) and DFS (5‐year survival rate, 92.7% vs 63.4%; P = 0.0004). According to our subgroup analyses, nine patients with positive non‐SLN had significantly shorter MSS compared with 32 patients with negative non‐SLN (5‐year survival rate, 32.4% vs 68.5%; P = 0.0273). The survival of 51 Japanese patients with acral lentiginous melanoma (ALM) was not inferior to the survival of patients with other Clark's subtype. Breslow thickness is an important factor for both MSS and DFS, and the status of SLN is the most predictive prognostic factor in Japanese patients with clinically localized melanomas, as in case of Caucasians. Features of ALM may be different between Asians and Caucasians.